The effect of external bleeding control training courses on lay first-person responders'knowledge, skills, and attitudes in low- and middle-income countries: a systematic review - Husham Abdelrahman (768893) (2025)
Background Exsanguinating hemorrhage is the most common cause of preventable trauma death at the injury scene, and it is often due to the inability to control bleeding immediately. Training layperson first responders (LFR) in trauma care, particularly hemorrhage control, has been recommended to address this trauma care gap. We conducted a systematic review (SR) to analyze the effect of hemorrhage control training courses for LFRs on knowledge, skill, and attitude to intervene in trauma patients. Methods PubMed and Google Scholar databases were used to identify relevant peer-reviewed research articles describing evaluations of hemorrhage control courses for LFR between 2013 and 2024. Studies examined whether the training course was implemented in low- and middle-income countries (LMICS); trainees were LFR and had outcome measures, including knowledge, skills, attitudes (confidence gained, willingness, comfort, and likelihood to intervene) toward care utilization for trauma patients, as well as outcomes. Results The SR included 12 articles. The quality of the selected studies was generally high. Five studies (42%) reported improved willingness, confidence, comfort, and the likelihood of responding safely to trauma. Nine studies (75%) used pre-and post-tests to document knowledge acquired, and five studies (42%) used knowledge retention evaluation at different intervals and reported substantial knowledge and skill reductions after a few months (1–3 months, 3–6 months, or both 6 and 9 months or up to 3 years). A few studies followed incident reports to document the utilization of knowledge and skills acquired during training. None reported patient outcomes. Conclusion Bleeding control training courses for layperson first responders in LMICS significantly improve knowledge, skill, confidence, and willingness to intervene to apply bleeding control techniques to trauma patients. Evaluating clinically relevant outcomes is needed to strengthen the evidence. Other Information Published in: European Journal of Trauma and Emergency Surgery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00068-025-02917-4